VD_FINDINFO ML / 2011 / 158 vom 16. August 2011 - VD Tribunal cantonal (2011)
RESTITUTION DU DÉLAI, MOYEN DE DROIT, DROIT D'OBTENIR UNE DÉCISION | 33 al. 4 LP, 147 al. 1 CPC (CH), 148 CPC (CH), 149 CPC (CH)